2009
DOI: 10.1002/pbc.21899
|View full text |Cite
|
Sign up to set email alerts
|

Non‐pineal supratentorial primitive neuro‐ectodermal tumors (sPNET) in teenagers and young adults: Time to reconsider cisplatin based chemotherapy after cranio‐spinal irradiation?

Abstract: This retrospective study demonstrates that non-pineal sPNET are clinically distinct from MB and are resistant to the Packer chemotherapy regimen. We suggest that it is time to reconsider the use of this regimen in teenage and young adult non-pineal sPNET and to investigate the utility of alternative approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 24 publications
0
34
0
1
Order By: Relevance
“…However, in another series of 33 patients with embryonal CNS tumor from [4]. The authors opined that nonpineal SPNET, especially in teenagers and young adults, is clinically distinct from MB and resistant to Packer's regimen and suggested the use of alternative chemotherapy (ifosfamide/temozolomide based) regimens [4]. Extrapolating from the data on the use of an alternating VAC and IE regimen in peripheral PNET and Ewing's sarcoma of bone (CCG-7881 and POG-8850 protocol), we follow alternating VAC/IEbased adjuvant chemotherapy for a total of 12 cycles after the completion of radiation therapy, and all but two patients received the aforementioned regimen in the current series [15].…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…However, in another series of 33 patients with embryonal CNS tumor from [4]. The authors opined that nonpineal SPNET, especially in teenagers and young adults, is clinically distinct from MB and resistant to Packer's regimen and suggested the use of alternative chemotherapy (ifosfamide/temozolomide based) regimens [4]. Extrapolating from the data on the use of an alternating VAC and IE regimen in peripheral PNET and Ewing's sarcoma of bone (CCG-7881 and POG-8850 protocol), we follow alternating VAC/IEbased adjuvant chemotherapy for a total of 12 cycles after the completion of radiation therapy, and all but two patients received the aforementioned regimen in the current series [15].…”
Section: Discussionmentioning
confidence: 94%
“…In another study of 22 patients, Reddy et al used eight cycles of a 6-weekly regimen of cisplatin, vincristine and lomustine after maximal safe resection and CSI with satisfactory results (5-year OS, 53 %) [36]. However, in another series of 33 patients with embryonal CNS tumor from [4]. The authors opined that nonpineal SPNET, especially in teenagers and young adults, is clinically distinct from MB and resistant to Packer's regimen and suggested the use of alternative chemotherapy (ifosfamide/temozolomide based) regimens [4].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…They occur mainly in the first decade of life, but they can also affect young adults [2]. Even though sPNETs have been grouped with medulloblastomas in many studies [3][4][5], their outcome is worse [2] and molecular studies have shown that sPNETs are distinct from medulloblastomas [6,7].…”
Section: Introductionmentioning
confidence: 98%